Synthesis, characterization and biological evaluation of novel thiourea derivatives - TOK, FATİH (My University, 2022)
Objective: A new series of 4-[3-(substitutedphenyl)thioureido]-N-(6-chloropyrazin-2-yl)benzenesulfonamide were synthesized from sulfaclozine. Methods: All compounds were characterized by IR, 1 H-NMR spectroscopic methods and elemental analysis. In addition to the antioxidant activity of the synthesis series, enzyme inhibition activities such as anticholinesterase, tyrosinase, α-amylase and α-glycosidase were determined for the first time in this study. Results: According to these biological activity test results, compound 2a in the DPPH, 2c in the ABTS˙+ assay exhibited more antioxidant activity than reference standard. All thiourea derivatives demonstrated good BChE inhibitory activity than galantamine. Among the compounds, 2e and 2f showed the best tyrosinase enzyme inhibition activity, while 2g had the best α-amylase and α-glucosidase enzyme inhibition activity. In addition, we evaluated the druglikeness properties of compounds and their oral bioavailability were also found to be high. Conclusion: Thiourea derivatives exhibited remarkable antioxidant activity and enzyme inhibition activity against tyrosinase, cholinesterase, α-amylase and α-glucosidase
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Thiourea; antioxidant; anticholinesterase; tyrosinase; alpha-amylase